Response of moth Plodia interpunctella to volatiles of fungus-infected and uninfected wheat grain. (October 2016) - Būda, Vincas; Apšegaitė, Violeta; Blažytė-Čereškienė, Laima; Butkienė, Rita; Nedveckytė, Irena; Pečiulytė, Dalė
Abstract: The aim of the study was to reveal volatile organic compounds (VOCs) produced by wheat grain, both before and after fungi infestation, which evoke reactions in Indian meal moth, Plodia interpunctella (Hübner) (Lepidoptera: Pyralidae), mated females. Solid phase micro-extraction (SPME) technique was used to collect volatiles and gas-chromatography, mass spectrometry (GC-FID/EAD, GC-MS) analysis and synthetic standards were applied to reveal and identify active compounds. Olfactory receptors of P. interpunctella females responded to five VOCs: 1-hexanol, nonanal, phenylacetaldehyde and 4-oxophorone (emitted by fungi-uninfected grain), and 3-methyl-1-butanol (emitted by fungi-infected grain). Behavioral tests carried out in olfactometers revealed attractive property of 1-hexanol and nonanal at low concentrations and repellent properties of 4-oxoisophorone to mated P. interpunctella females. Phenylacetaldehyde was neither an attractive nor repellent. 3-Methyl-1-butanol acted as an attractant at low concentrations and as repellent at higher ones. The latter compound could serve as a kairomone and allomone due to its different effects on behavior at higher and lower concentration. Highlights: Plodia interpunctella females responded to five VOCs emitted by fungi-uninfected grain. P. interpunctella females responded to 3-methyl-1-butanol emitted by fungi-infected grain. 1-Hexanol and nonanal at low concentrations are attractive to P. interpunctella females. 4-Oxoisophorone acted as repellent towards mated P. interpunctella females. 3-Methyl-1-butanol is attractive at low concentrations and repellent at higher ones.